Metamorfosis Bayang: Revitalisasi Semesta Wayang dalam Praktik Seni Rupa Kontemporer dan Transmedia Indonesia - Wiratno, Tri Aru (Faculty of Arts and Design, Jakarta Institute of the Arts, 2026)
This article explores the representation of the wayang universe within Indonesia's contemporary visual culture landscape through a critical revitalization approach. Wayang is no longer viewed as a static artifact of tradition, but rather as a dynamic sign system that continuously mutates in contemporary fine arts and transmedia narratives. Utilizing a descriptive qualitative method along with an in-depth literature study, this research reveals that current revitalization practices occur through visual deconstruction and massive digital technology adaptation.The findings indicate that the wayang universe serves as an elastic bridge for national identity, capable of adapting to new media—such as kinetic installations, films, and digital platforms—without losing its philosophical essence. The novelty of this study lies in identifying the concept of